2009
DOI: 10.1001/archsurg.2009.191
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes From 3144 Adrenalectomies in the United States

Abstract: To optimize outcomes, patients with adrenal disease should be referred to surgeons based on adrenal volume and laparoscopic expertise irrespective of specialty practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(60 citation statements)
references
References 36 publications
0
59
0
Order By: Relevance
“…2–5 Previous studies have demonstrated that increased surgical volume is an independent predictor of lower rates of postoperative complications and shorter length of stay for patients undergoing adrenalectomy in the United States and Spain. 18,19 Furthermore, greater surgical experience has been associated with improved oncologic outcomes for patients with ACC. For example, Kerkhofs et al evaluated patients with stage I to III ACC followed in the National Cancer Registry in the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…2–5 Previous studies have demonstrated that increased surgical volume is an independent predictor of lower rates of postoperative complications and shorter length of stay for patients undergoing adrenalectomy in the United States and Spain. 18,19 Furthermore, greater surgical experience has been associated with improved oncologic outcomes for patients with ACC. For example, Kerkhofs et al evaluated patients with stage I to III ACC followed in the National Cancer Registry in the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…This is a potential source of selection bias because large and academic institutions are over-represented. However, there is evidence that a significant proportion of complex cases are performed by ACS-NSQIP institutions and that up to two thirds of adrenalectomies are performed at teaching hospitals, which suggests that this database likely captures a large numbers of adrenalectomies performed nationally 17, 18 . A significant limitation is the failure of ICD-9 codes to adequately identify the principal diagnosis of patients undergoing adrenalectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Although obesity is often considered a risk factor for postoperative complications, various studies conclude contradictory results [10,11]. LA presents lower rates of complications and mortalities than conventional open surgery, and surgeons' experience would further help to improve perioperative outcomes [12,13]. To our knowledge, convincing evidence for the impact of obesity on LA has not been acquired.…”
Section: Introductionmentioning
confidence: 99%